Teledentistry awareness, its usefulness, and challenges among dental professionals in Pakistan and Saudi Arabia. (March 2022) - Chaudhary, Farooq Ahmad; Ahmad, Basaruddin; Javed, Muhammad Qasim; Mustafa, Saeed; Fazal, Ayesha; Javaid, Muhammad Mohsin; Siddiqui, Ammar Ahmed; Alam, Mohammad Khursheed; Ud Din, Shahab
Objectives: This study aims to describe the perception of dental professionals in Pakistan and Saudi Arabia (SA) towards the practice of teledentistry, its usefulness and challenges. Methods: A cross-sectional study was carried out among 190 dentists from January 2021 to April 2021. The participants were included in the study using snowball sampling method. A 26-item adopted questionnaire was distributed using different social media channels. Chi-square test was used for analysis. Results: Out of 190 participants, 46.3% were from Pakistan and 53.7% were from SA. The majority of participants in both countries agreed that teledentistry would enhance guidelines and advice (74.2%), improve peer-to-peer interaction (79.5%) and make patient's referrals more efficient (75.8%). For the usefulness, most participants agree that it is economical for the patients (61.1%), improves communication (74.7%), helps in educating the patients (86.3%), avoid unnecessary travel (76.8%), helps monitoring (71.6%), and benefits patients in remote areas (74.7%); however, more Pakistani participants perceived that time spent with the patient would increase compared to SA participants ( p  < 0.001) and a higher proportion of SA participants believe that it helps in communication and monitoring of patients ( p  < 0.001) than Pakistani participants. Regarding the challenges in the use of teledentistry, few participants think that it violates the patient's privacy (22.6%) or is difficult to use (14.7%) or have distrust towards the teledentistry equipment (24.2%). Conclusion: The results indicated a high awareness and a positive attitude towards teledentistry, and its adaptation in their dental practice in both countries. However, limited infrastructure, set-up cost, and information technology (IT) literacy are the main challenges in integrating teledentistry which can be overcome by strategic government initiatives, policies, and programs.